2019
DOI: 10.1507/endocrj.ej19-0053
|View full text |Cite
|
Sign up to set email alerts
|

Annual change in plasma xanthine oxidoreductase activity is associated with changes in liver enzymes and body weight

Abstract: Xanthine oxidoreductase (XOR), an enzyme of uric acid formation from hypoxanthine and xanthine, is recognized as a source of oxidative stress. Plasma activity of XOR has been reported to be a biomarker of metabolic disorders associated with obesity, liver dysfunction, insulin resistance, hyperuricemia and adipokines. We investigated longitudinal change in plasma XOR activity, which was determined by using mass spectrometry and liquid chromatography to detect [ 13 C 2 , 15 N 2 ]-uric acid using [ 13 C 2 , 15 N … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 26 publications
1
9
1
Order By: Relevance
“…Together, these results suggest that XOR contributes to increase BP, at least in part via endothelial dysfunction through ROS production. Importantly, VFA (ρ = 0.513, p < 0.001) and HbA1c (ρ = 0.260, p = 0.001) were positively correlated with plasma XOR activity, which is consistent with previous reports including ours showing that obesity and glycemic control level are positively associated with plasma XOR activity 20,21 . Visceral fat accumulation and diabetes are known to be risk factors for development of hypertension, though the underlying mechanisms have yet to be fully elucidated.…”
Section: Discussionsupporting
confidence: 91%
“…Together, these results suggest that XOR contributes to increase BP, at least in part via endothelial dysfunction through ROS production. Importantly, VFA (ρ = 0.513, p < 0.001) and HbA1c (ρ = 0.260, p = 0.001) were positively correlated with plasma XOR activity, which is consistent with previous reports including ours showing that obesity and glycemic control level are positively associated with plasma XOR activity 20,21 . Visceral fat accumulation and diabetes are known to be risk factors for development of hypertension, though the underlying mechanisms have yet to be fully elucidated.…”
Section: Discussionsupporting
confidence: 91%
“…To date, few studies have evaluated changes in the XOR activity. It was recently reported that, in a population‐based cohort, an annual change in plasma XOR activity was independently associated with a change in bodyweight, as well as that in liver enzymes 20 . In the present study, changes in bodyweight and BMI did not correlate with those in plasma XOR activity.…”
Section: Discussionmentioning
confidence: 99%
“…An accurate and sensitive assay for activity of plasma XOR in humans has been newly developed using liquid chromatography and triple quadrupole mass spectrometry to measure [ 13 C 2 , 15 N 2 ]‐uric acid using [ 13 C 2 , 15 N 2 ]‐xanthine as a substrate. Using this assay, we and others have shown that activity of plasma XOR is a novel metabolic biomarker associated with obesity, insulin resistance, hyperuricemia, liver dysfunction and adipokines. Furthermore, we showed unexpected high activity of plasma XOR in some hyperuricemic patients by using an XOR inhibitor and in some female relatively hypouricemic patients .…”
Section: Introductionmentioning
confidence: 86%